Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Văn học, 2004)
Võ Huy Tâm; Nguyễn Thị Cẩm Thạnh; Nguyễn Quang Thân; Bùi Bình Thi; Nguyễn Đình Thi; Nguyễn Thi; Xuân Thiều; Bích Thuận.